Students’ Perceptions and Understanding of TEIL-Based Teaching Materials - Adzima Madiena, Noor; Syah Putra, Aidil; Syifa, Zahratus; Noviyanti, Noviyanti (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This study aims to investigate students’ perceptions and understanding of Teaching English as an International Language (TEIL)-based teaching materials in an EFL context. The research employed a qualitative descriptive approach involving 15 English Education students at Universitas Muhammadiyah Tangerang who had experienced the use of TEIL-oriented materials in their learning process. Data were collected through classroom observation and semi-structured interviews. The findings reveal that students generally perceived TEIL-based teaching materials positively in terms of relevance, clarity, and usefulness. The materials helped students develop a broader understanding of English as a global means of communication and increased their awareness of diverse English varieties. Furthermore, students reported that TEIL-based materials enhanced their confidence in using English for international communication and reduced anxiety related to native-speaker norms. This study suggests that integrating TEIL principles into English teaching materials can contribute to more inclusive and contextually relevant English language learning in EFL settings.